The Grid and CRM: from "If" to "When" - Lloyd, Ashley (Elsevier Science, 2005)
The "Grid", an initiative of the distributed computing community, offers unprecedented levels of computing power for organisations to apply to solving their business problems. Uniquely it also offers the communications infrastructure required to overcome the "tyranny of distance" observed by Blainey (The Tyranny of Distance, Melbourne:Sun Books) in his analysis of the socio-economic development of Australia. However, recent reports of the "death of distance" and consequent strategies of trans-nationalcompanies to centralise their operations are tempered by reports of a growing "psychic" distance with their customers. This paper reports the application of high-performance computing (HPC) to modelling consumer behaviour within a large UK financial services company in order to predict not only "if" a certain type of customer behaviour was likely to occur, but also "when". The resultant impact on their customer relationship management strategy leads to the observation that Grid Computing should offer many new opportunities for managing the problem of "psychic" distance that attends a strategy of revenue growth through widening the geographic scope of operations, and scale efficiencies through physical centralisation.